2020
DOI: 10.1155/2020/4892415
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Quercetin on Anxiety‐Like Symptoms and Neuroinflammation Induced by Lipopolysaccharide in Rats

Abstract: Recently, neuroinflammation is thought to be one of the important causes of many neuropsychiatric diseases. Quercetin (QUER) is a natural flavonoid, and it is well known that QUER has antioxidative, anti-inflammatory, and neuroprotective effects. In our study, lipopolysaccharide (LPS) was injected into the lateral ventricle of rats to induce anxiety-like behaviors and neuroinflammation, and it was confirmed that chronic administration of QUER could improve anxiety-like symptoms. We also investigated the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 28 publications
2
28
0
1
Order By: Relevance
“…Zhang et al [38] reported that quercetin exerted the beneficial or detrimental effects on the shoaling and anxiety behaviors in zebrafish depending on the treatment concentrations, and the underlying mechanisms are potentially associated with neuroinflammation and neuron apoptosis. Quercetin inhibited anxiety-like symptoms and neuroinflammation induced by lipopolysaccharide in rats as stated by Lee et al [39]. Quercetin mitigated anxiety-like behavior and normalized hypothalamus-pituitary-adrenal axis function in a mouse model of mild traumatic brain injury as reported by Kosari-Nasab et al [40].…”
Section: Novel Tank Diving Test (Ntt)mentioning
confidence: 77%
“…Zhang et al [38] reported that quercetin exerted the beneficial or detrimental effects on the shoaling and anxiety behaviors in zebrafish depending on the treatment concentrations, and the underlying mechanisms are potentially associated with neuroinflammation and neuron apoptosis. Quercetin inhibited anxiety-like symptoms and neuroinflammation induced by lipopolysaccharide in rats as stated by Lee et al [39]. Quercetin mitigated anxiety-like behavior and normalized hypothalamus-pituitary-adrenal axis function in a mouse model of mild traumatic brain injury as reported by Kosari-Nasab et al [40].…”
Section: Novel Tank Diving Test (Ntt)mentioning
confidence: 77%
“…Among the compounds found to be associated with better cognitive health in our study, flavonols and flavanones have been shown to increase the transforming growth factor-β1 (TGF-β1) levels [ 42 , 43 ], a neurotrophic factor that exerts a key role in recognition memory formation, and a deficit of TGF-b1 signaling can contribute to cognitive decline in Alzheimer’s disease [ 44 , 45 ]. With special regard to quercetin (a flavonol found related to better cognitive health in our study), it has demonstrated effectiveness in animal models of Alzheimer’s disease in decreasing of oxidative stress [ 46 ] and positively modulating Nrf2/HO-1 (nuclear factor erythroid 2–related factor 2/heme oxygenase-1) pathway [ 47 ]; also, an effect toward neuro-inflammation through regulation of NF-κB (nuclear factor kappa-light-chain-enhancer of activated B cells) and has been observed [ 48 ]. Furthermore, quercetin has been shown to induce the expression of a brain-derived neurotrophic factor (BDNF) [ 49 ] as well as a nerve growth factor (NGF) [ 50 ], which are the most studied and best-characterized neurotrophins of the central nervous system, involved in the modulation of synaptic plasticity and adult neurogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroprotective effects of quercetin and kaempferol are widely documented in various experimental models, which are associated, either directly or indirectly, with modulation of autophagy and immunoproteasome pathways. These include reduction of oxidative stress and neuroinflammation, induction of M2 microglia polarization, improvement of BBB function, prevention of AGE/RAGE-related neuronal damage, inhibition of HMBG1/TLR4 axis, and activation of AMPK and Nrf2 [ 200 , 201 , 202 , 203 , 204 , 205 , 206 ]. Both quercetin and kaempferol, through inhibition of cytochrome P-450-dependent catalysis, prevent the hepatic metabolism of 17 beta-estradiol [ 207 ], whose effects are bound to autophagy activity [ 208 ] and are potentially relevant in the frame of either influenza virus or COVID-19 pathogenesis [ 209 , 210 ].…”
Section: Anti-viral and Anti-inflammatory Effects Of Phytochemicalmentioning
confidence: 99%